Detection of Salmonella sp. on Layer Chicken Eggs Sold at The Vegetable Market of Magetan Regency - Brillian Inawulan Syamsiar; Kuncoro Puguh Santoso; Ira Sari Yudaniayati; Diyantoro Diyantoro (Universitas Airlangga, 2020)
Background: Eggs are poultry products that cannot be separated from the possibility of Salmonella contamination. Traditional markets are places where consumers can get chicken eggs with poor hygiene and sanitation aspects. Habits of today's society that often consumes raw or undercooked eggs can trigger Salmonellosis. Purpose: To identify the presence of Salmonella sp. in eggs sold in Magetan Regency Vegetable Market. Method: Sampling of eggs from different random stores. The eggs then proceeded with selection pre-enrichment, selective enrichment, isolation, and identification. Results: The handling of eggs in the Magetan Regency Market was quite good in its storage period, and purebred eggs sold in the Magetan Regency Market were negatively contaminated with Salmonella sp. Conclusion: Broiler chicken eggs sold in Magetan Vegetable Market are safe to consume.